Low-molecular-weight heparins utilization in pregnant and postpartum women: a real-world analysis in China (2016–2021) - Liu, Hao-Ran; Sun, Kai; Zeng, Tao; Wang, Xian-Li (Frontiers in Pharmacology, 2025)
ObjectivesThis study aimed to examine trends in low-molecular-weight heparin (LMWH) use for managing pregnancy-associated venous thromboembolism (VTE) and to explore the correlation between pregnancy-related VTE risk factors and LMWH prescription rates.MethodsThis was a cross-sectional study that analyzed prescription data from pregnant and postpartum women using LMWH to manage VTE, collected during 2016–2021. Risk factors associated with VTE were analyzed. Separately comparing the number of prescriptions, prescription cost, defined daily doses (DDDs), and defined daily cost (DDC) of seven LMWH.ResultsThis study included 41,885 prescriptions, with the average age of patients being 32 ± 4.69 years old. The most common risk factors for VTE during pregnancy and the postpartum period in this study included advanced age (>35 years old), cesarean section, diabetes, miscarriage, and preterm birth, accounting for 28.61%, 25.60%, 18.34%, 17.31%, and 13.63% respectively. There was a 173% increase in LMWH prescription costs during the study period. In terms of number of prescriptions, prescription cost, and DDDs, enoxaparin sodium, nadroparin calcium, and low-molecular-weight heparin calcium consistently ranked in the top three from 2019 to 2021. In terms of DDC, low-molecular-weight heparin sodium, dalteparin sodium, and enoxaparin sodium were the lowest.ConclusionFrom 2016 to 2021, both the number of prescriptions and the total prescription costs for the management of VTE during pregnancy and the postpartum period increased. Enoxaparin sodium, nadroparin calcium, and low-molecular-weight heparin calcium were the most common LMWH. Advanced age (>35 years old), cesarean section, diabetes, miscarriage, and preterm birth were the most common pregnancy-related VTE risk factors linked to LMWH prescription.